تطبيق الطريقة للعبة الهمسية المتسلسلية لتحْسين مَهَارَةِ اَلاِسْتِمَاعِ في اَلْمَدْرَسَةِ المتوسطة مفتاح الجنة بروبولنجو - Utami, Sri Idhom; Yunus, Moch.; Shobirin, Shobirin (MASALIQ, 2025)
Listening is one of the essential skills in learning the Arabic language, as it contributes to the development of speaking, reading and writing skills. It is defined as the ability to understand the information and intentions of spoken language in different situations. This research aims to clarify the impact of the application of the sequential whispering game in improving the listening skill of the students of Miftah Al-Jana Islamic Middle School in Probolinggo. This game is considered an interactive educational tool that creates a fun atmosphere in the classroom. The research relied on the descriptive qualitative method, through observation, interview, and documentation. The results showed that this method contributes to raising the students’ concentration and increasing their interaction, and a clear improvement in their ability to understand the information heard in Arabic was observed. Accordingly, the chain whisper game can be considered an effective method that helps develop listening skills in a fun and effective way.